Оптимізація впливу регіональних структур управління на сталий розвиток індустрії туризму та гостинності: міжнародний досвід - Якименко-Терещенко, Наталія Василівна; Чайка, Тетяна Юріївна; Холодок, Валентина Дмитрівна (Видавничий дім "Гельветика", 2023)
Метою статті є аналіз можливих проблем, вивчення зарубіжних практик та розробка рекомендацій щодо оптимізації змісту, форм, методів і інструментів взаємодії регіональних структур управління з представниками індустрії туризму і гостинності на шляху до сталого розвитку. Актуальність теми дослідження пов'язана з високою соціально-економічною та екологічною значимістю впровадження концепції сталого розвитку з точки зору забезпечення довгострокового благополуччя усієї світової спільноти. Аналіз наявних проблем, з якими стикається туристичний та готельно-ресторанний бізнес на шляху до впровадження стійких практик, дозволив зробити висновок про необхідність колаборації місцевого самоврядування, корпорацій та закладів освіти з метою створення освітніх продуктів формату lifelong learning (освітніх курсів, вебінарів, майстер-класів, сертифікатних програм тощо). Тематика таких освітніх продуктів має бути спрямована на підвищення обізнаності представників туристичного та готельно-ресторанного бізнесу про цілі сталого розвитку та практичні шляхи їх досягнення.

The aim of this paper is to examine problems that may accompany the interaction between regional governance structures and representatives of the tourism and hospitality industry on the way to sustainable development; to study foreign practices and develop recommendations to optimize the content, forms, methods and tools to promote sustainable development of tourism and hospitality industry at the local level. The relevance of the research topic is linked to the high social, economic and environmental significance of implementing the concept of sustainable development in terms of the long-term well-being of the entire global community. The Sustainable Development Goals cannot be achieved without the active participation of all sectors of the economy, including the tourism and hospitality industry. The search for optimal methods, forms, tools of interaction of regional governance structures with representatives of tourism and hospitality business in the context of implementation of successful practices of sustainable development is an important component of the success of efforts to achieve sustainable development goals. When studying foreign experience, problems and promising trends of development of interaction of local authorities with representatives of tourism and hospitality industry, logical-analytical and system-structural methods of research were used. The paper notes that the focus should be on achieving those sustainable development goals that are currently outsiders. The directions for achieving the goals of sustainable development in relation to the tourism and hospitality industry have been clarified. The main challenges faced by the tourism and hospitality industry in adopting sustainable practices were identified. These include: incompatibility of business models with the goals of sustainable development; lack of awareness among business representatives of the concept and objectives of sustainable development; lack of practical recommendations for achieving sustainable development goals taking into account sectoral and regional specifics; inconsistency in efforts of sustainable development actors at the regional level. The analysis of existing problems has led to the conclusion that there is a need for collaboration between local governments, corporations and educational institutions to create lifelong learning educational products (educational courses, webinars, master classes, certificate programmes). The subject matter of such educational products should be aimed at raising awareness of the tourism and hospitality industry about the goals of sustainable development.
Optimizing the impact of regional governance structures on the sustainable development of the tourism and hospitality industry: international experience
Keywords: регіональні структури управління; сталий розвиток; міжнародний досвід; туризм; готельно-ресторанний бізнес; оптимізація; цілі сталого розвитку; колаборація; навчання протягом усього життя; regional governance structures; sustainable development; international experience; tourism; hospitality; optimization; sustainable development goals; collaboration; lifelong learning